2007
DOI: 10.3310/hta11210
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost-effectiveness of treatments for children with idiopathic steroid-resistant nephrotic syndrome: a systematic review

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 71 publications
1
14
0
2
Order By: Relevance
“…This compares with the ISKDC study, where nearly 80% of patients with NS were found to be steroid-responsive, and less than 50% of these patients had either FR or SD, with 85% disease free at 10 years [54,55]. While the frequency of steroid-responsive NS in patients with C1q nephropathy seems to be much lower and the frequency of ESRD much higher than has been reported in the pediatric NS literature [56][57][58], many of the C1q nephropathy case series are heavily biased toward a steroid-resistant population.…”
Section: Clinical Correlationssupporting
confidence: 51%
“…This compares with the ISKDC study, where nearly 80% of patients with NS were found to be steroid-responsive, and less than 50% of these patients had either FR or SD, with 85% disease free at 10 years [54,55]. While the frequency of steroid-responsive NS in patients with C1q nephropathy seems to be much lower and the frequency of ESRD much higher than has been reported in the pediatric NS literature [56][57][58], many of the C1q nephropathy case series are heavily biased toward a steroid-resistant population.…”
Section: Clinical Correlationssupporting
confidence: 51%
“…However, we found no statistically significant difference in hospitalization days and costs of hospitalization. Evidence on pharmacoeconomic evaluation of treatments for SRNS need to be identified to provide guidance for clinical practice (33).…”
Section: Discussionmentioning
confidence: 99%
“…vincristine), antiproliferative immunosuppressants [e.g. mycophenolate mofetil (MMF), calcineurin inhibitors (CI) cyclosporin A and tacrolimus], immunomodulating drugs (levamisole), angiotensin converting enzyme inhibitors (ACE-I) and plasma exchange, are used [1,4]. Many of these treatments have significant side effects and are not always effective.…”
Section: Introductionmentioning
confidence: 99%